1976
DOI: 10.1103/physrevb.13.835
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropy of structural models for amorphous materials

Abstract: Correlations responsible for anisotropic-scattering properties of close-packed and tetrahedrally coordinated amorphous-model structures are discussed. It is shown that although there are regular planes of high density associated with the strong-scattering directions, the scattering anisotropy is not very different from that which occurs for random scattering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

1977
1977
2011
2011

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Gaskell and Wallis [13] calculated the anisotropic scattering, S(Q) for jQj = Q 1 , from models for a-SiO 2 using the method described by Alben et al [16]. They concluded that the highest values of the anisotropic intensity, in those models that were most successful in describing the FSDP in silica, were associated with planar fluctuations in atomic density.…”
Section: Lqs In Models With Medium-range Ordering Based On Crystal Momentioning
confidence: 98%
“…Gaskell and Wallis [13] calculated the anisotropic scattering, S(Q) for jQj = Q 1 , from models for a-SiO 2 using the method described by Alben et al [16]. They concluded that the highest values of the anisotropic intensity, in those models that were most successful in describing the FSDP in silica, were associated with planar fluctuations in atomic density.…”
Section: Lqs In Models With Medium-range Ordering Based On Crystal Momentioning
confidence: 98%
“…Here, the concepts of randomness become useful. The relation quoted by Alben et al [11], shows that there is a probability of 0.1 that chance correlations from a random model of this size would lead to I(Q) values greater than about 8 times the average intensity. Fig.…”
Section: Medium-range Structurementioning
confidence: 91%
“…Fig. 2b shows an even more extreme distribution of the scattered intensity [12] for a section of Finney's 7994-atom, dense random packed model for an amorphous metal [13], where the maximum intensity is almost 14 times the average [11]. This is what examination of anisotropy in CRN models can offer, emphasising the potential value of data extracted from anisotropic scattering in real materials.…”
Section: Medium-range Structurementioning
confidence: 94%
See 2 more Smart Citations